Comparacao entre os valores da pressao arterial central e braquial em portadores de hipertensao arterial sistemica - Pelazza, Bruno Bordin (2012)
Introduction: Systolic blood pressure (SP) and pulse pressure (PP) rise gradually during the aging process as a consequence of a reduction in arterial elasticity. The measure of systemic arterial pressure (SAP) taken at the root of the aorta has been considered an independent determinant of cardiovascular mortality superior to the values of brachial SAP. Aim: To compare the values of SAP central to those of braquial SAP in patients of different age brackets who have systemic hypertension. Method: We evaluated the central SAP at the root of the aorta and the brachial SAP in the left arm using the ocillometric method 244 hypertensive patients who had been submitted to cineangiocoronarography. Five groups of patients were constituted: Group I, 39-49, n=36, Group II, 50-59, n=67, Group III, 60-69, n=69, Group IV, 70-79, n=46, Group V ≥ 80 y.o, n=26. Results: When central SP was compared to brachial SP, it was possible to find significance in patients who were 50 y.o and upwards. It was not possible to find a statistical difference between central diastolic pressure and brachial except in patients between the ages of 60-69. When comparing central to brachial PP, we observed that central PP was significantly greater (between 11 and 15 mmHg) in all patient above the age of 50. Conclusion: In older people, the values of SP and PP, taken directly at the root of the aorta, are superior to those obtained by indirect means from the brachial artery. These differences are significant from the age of 50 onwards.